Overview of sesquiterpenes and chromones of agarwood originating from four main species of the genus Aquilaria. Issue 8 (30th January 2019) - Gao, Mei; Han, Xiaomin; Sun, Ying; Chen, Hongjiang; Yang, Yun; Liu, Yangyang; Meng, Hui; Gao, Zhihui; Xu, Yanhong; Zhang, Zheng; Han, Jianping
Abstract : The main compounds in agarwood (sesquiterpenes and chromones) are classified and summarized based on their molecular skeletons and plant species. Abstract : The main chemical constituents of agarwood are sesquiterpenes and chromones, which can be divided into different categories depending on their molecular skeletons. Agarwoods are obtained from different plant species: Aquilaria sinensis, A. malaccensis, A. crassna, and A. subintegra . In this review, we systematically summarized the structures of 367 compounds isolated from agarwoods originating from four main species. We structurally classified all the components into 11 different types and summarized the number of compounds in each type. Different and identical components were obtained by enumerating the chemical compositions of the different species. Knowledge regarding the chemical constituents of agarwoods of different species will aid understanding of the chemical compositions of agarwoods and will subsequently identify similar compounds that can serve as standards for quality control to provide a reference for future studies on agarwoods from different species and to increase their usefulness.